الخطاب الدعوي عند الشيخ محمد البشير الإبراهيمي مضامينه ووسائله - سعدين, عفيفة; عبيدي, منى (University of Eloued-جامعة الوادي, 2022)
" تناولت هذه الدراسة موضوع الخطاب الدعوي عند الشيخ محمد البشير الإبراهيمي مضامينه ووسائله, فتحدثنا عن التعريف بجمعية العلماء المسلمين نشأتها والظروف المحيطة بها والمبادئ التي قامت عليها والأهداف التي سعت لتحقيقها. كما تطرقنا أيضا في هذه الدراسة إلى التعريف بالشيخ البشير الإبراهيمي الذي هو يعد علم من أعلام الجزائر, حيث سخر علمه وقلمه لخدمة وطنه واعتنى به عناية عظيمة بإصلاح ما أفسده الاستعمار, واهتمَّ بذلك اهتماما كبيرا . كما تطرقنا في هذه الدراسة إلى المضمون العقدي والتربوي والاجتماعي والسياسي عند الشيخ الإبراهيمي, وقد عرجنا على بيان الوسائل التي استعملت في توصيل هذا الخطاب فذكرنا المسجد والصحافة ودور التعليم والجمعيات والنوادي. وفي الخاتمة تحدثنا عن النتائج والتوصيات. ""This studydealtwith the subject of the advocacy speech of Sheikh Muhammad al -Bashir al -Ibrahimi, its contents and means, sowetalked about the definition of the Association of MuslimScholars, itsorigins, the surroundingcircumstances, the principles on whichitwasbased, and the goals thatitsought to achieve. Wealsotouched on thisstudy to introduce Sheikh Al -Bashir Al -Ibrahimi, whoisconsidered one of the flags of Algeria, as hemockedhis flag and hispen to serve his country and took care of himwithgreat care to reformwhatwasspoiled by colonialism, and hewasinterested in greatinterest. In thisstudy, wealsotouched on the contractual, educational, social and political content of Sheikh Al -Ibrahimi, and we have shown the statement of the meansthatwereused to communicatethis speech, sowementioned the mosque, the press, the role of education, associations and clubs. In conclusion, wetalked about the results and recommendations. "
مذكرة ماستر
Keywords: محمد البشير الإبراهيمي، مضامينه، وسائله، جمعية العلماء; Muhammad al-Bashir al-Ibrahimi, its contents and methods, the Association of Scholars